Germination Studies on a few Multipurpose Nitrogen Fixing Tree Species Used in Afforestation Programmes in Central Himalaya - Rana, Urmila; Rao, K. S. (Indian Forester, 1997)
In this study better germination was obtained by mechanical scarification for Acacia farnesiana, A. benthemii, Albizia lebbek and Cassia fistula. Though it will be difficult to implement in nursery requiring large stocks, the effeort is recommended as germination rates increased many fold over other treatments and control, thus requiring less seed for achieving large uniform stock.